SSRI treatment decreases prolactin and hyperthermic responses to mCPP. - Quested, D; Sargent, P; Cowen, P (1997)
We studied the effect of 3 weeks treatment with the selective serotonin re-uptake inhibitor (SSRI), paroxetine (30 mg daily), on the neuroendocrine and hyperthermic responses to the 5-HT2C receptor agonist, m-chlorophenylpiperazine (mCPP) (0.05 mg/kg i.v.), in seven healthy volunteers. Following paroxetine treatment, both the prolactin and hyperthermic responses to mCPP were significantly attenuated. These data are consistent with experimental animal studies indicating that repeated SSRI treatment leads to a functional desensitisation of 5-HT2C receptors. This effect may be linked to the anxiolytic properties of SSRIs.